2016
DOI: 10.1007/s41669-016-0007-y
|View full text |Cite
|
Sign up to set email alerts
|

Utilization, Spending, and Price Trends for Quinolones in the US Medicaid Programs: 25 Years’ Experience 1991–2015

Abstract: BackgroundGiven that the quinolones is one of the antibacterial classes most frequently used to treat patients with bacterial infections in the United States, any change in prescribing patterns of quinolones will impact Medicaid medical expenditures.ObjectivesThis study was undertaken to examine trends in utilization, reimbursement, and prices of quinolone antibacterials for the US Medicaid population.MethodsThe publicly available Medicaid State Drug Utilization outpatient pharmacy files were used for this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…The Centers for Disease Control and Prevention (CDC) reported a rise in outpatient fluoroquinolone use between 1991 and 2010 that plateaued between 2011 and 2015. 6 A Veterans' Health Administration study showed a non-statistically significant decline in inpatient fluoroquinolone use as a percentage of all antimicrobials between 2007 and 2015. 7 A review of a drug database that included inpatient antimicrobial use data from >300 US hospitals found a nearly 20% decrease in fluoroquinolone use between 2006 and 2012.…”
Section: Discussionmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention (CDC) reported a rise in outpatient fluoroquinolone use between 1991 and 2010 that plateaued between 2011 and 2015. 6 A Veterans' Health Administration study showed a non-statistically significant decline in inpatient fluoroquinolone use as a percentage of all antimicrobials between 2007 and 2015. 7 A review of a drug database that included inpatient antimicrobial use data from >300 US hospitals found a nearly 20% decrease in fluoroquinolone use between 2006 and 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, FQs are one of the most commonly prescribed classes of antibiotics, with ϳ30 million oral prescriptions for FQs being dispensed in the United States in 2014 (7). Use of FQs has increased dramatically over time, with a reported 245.5% increase in Medicaid payments for quinolone agents between 1991 and 2015 (7,8).…”
mentioning
confidence: 99%
“…Indeed, levofloxacin and ciprofloxacin appear both on the list of the most used antibiotics (data related to prescriptions reimbursed by the Italian Health System in 2018) in Italy together with amoxicillin and clavulanic acid, ceftriaxone, cefixime, and fluconazole (Italian Medicine Agency, 2017). The well-established use of levofloxacin and ciprofloxacin is not a prerogative of the Italian pharmaceutical market rather it is extended to other countries, including the US where both drugs dominated the antibiotic pharmaceutical market for almost 20 years (Almalki et al, 2017). From the same observation, it is possible to deduce that the lower number of ICSRs related to first-generation quinolones could be related to their lower use in the clinical practice.…”
Section: Discussion Icsrs Involving Quinolones In the Italian Spontanmentioning
confidence: 99%
“…According to Belliveau PP et al, almost 46% of levofloxacin prescriptions were replaceable by other conventional antimicrobial therapies (Belliveau et al, 2000). Literature data suggest that two main reasons may underline the higher prescription of quinolones, including the fact that prescribers intend to use a broader-spectrum agent than necessary and, second, since patients expect to be prescribed medication at the end of the visit, clinicians tend to increase their antibacterial-prescribing habit to ensure the patients are satisfied with their care (Almalki et al, 2017).…”
Section: Agementioning
confidence: 99%